Ischaemic preconditioning : an investigation of the patterns of kinase activation and protein expression profiles during reperfusion in the rat heart - Hattingh, Susanna Maria (Suzel) (Stellenbosch : Stellenbosch University, 2013)
Thesis (PhD)--Stellenbosch University, 2013.